Cold War spy stories from Eastern Europe - Glajar, Valentina; Lewis, Alison; Petrescu, Corina L. (2019)
"With the opening of the secret police archives in many countries in Eastern Europe comes the unique chance to excavate many forgotten spy stories and narrate them for the first time. 'Cold War Spy Stories from Eastern Europe' brings together a wide range of Cold War spy stories from the Eastern Bloc and explores stories compiled from the East German Stasi, the Romanian Securitate, and the Ukrainian KGB files"..